Identifying patient-important outcomes for treatment of bipolar disorder: a systematic review protocol. Issue 12 (30th December 2021) - D'Elia, Alessia; Orsini, Olivia; Sanger, Stephanie; Hillmer, Alannah; Sanger, Nitika; Panesar, Balpreet; Rodrigues, Myanca; Kapczinski, Flavio; Thabane, Lehana; Samaan, Zainab
Abstract : Introduction: Treatment of bipolar disorder is the focus of several clinical trials, however the understanding of the outcomes for establishing treatment effectiveness within these trials is limited. Further, there is limited literature which reports on the outcomes considered to be important to patients, indicating that patient perspectives are often not considered when selecting outcomes of effectiveness within trials. This protocol describes a systematic review which aims to describe the outcomes being used within trials to measure treatment effectiveness, commenting on the inclusion of patient-important outcomes within previous trials. Methods and analysis: This protocol is reported using the Preferred Reporting Items for Systematic Reviews and Meta-analyses Protocols statement. OVID MEDLINE, OVID Embase, OVID APA PsycINFO, Web of Science, the Wiley Cochrane Library, ClinicalTrials.gov and the International Clinical Trials Registry Platform databases will be searched for eligible studies. Screening, full-text and data extraction stages will be completed in duplicate using the Covidence platform for systematic reviews. Eligible studies will include clinical trials of interventions in bipolar disorder, in order to identify outcomes used to assess treatment effectiveness, and qualitative studies, to determine which outcomes have been reported as important by patients. Risk of bias for included studies will be assessed using the Cochrane Risk of Bias Tool for randomised controlled trials, and the Newcastle-Ottawa Scale for observational research. Ethics and dissemination: This review will involve dissemination to key stakeholders, including primary end users such as patients, clinicians and trialists. Knowledge translation tools will be generated to share the relevant conclusions of this review. Results will be communicated to the scientific community through peer-reviewed publications, conferences and workshops. No ethics approval will be sought as this study is based on literature. PROSPERO registration number: CRD42021214435.